PENGARUH PEMBELAJARAN TIME TOKEN DILENGKAPI LEMBAR KERJA TERHADAP KOMPETENSI BELAJAR MAHASISWA DI APIKES IRIS PADANG - sari, rahmi septia (Universitas PGRI Sumatera Barat, 2019)
This study aims to determine the effect of applying the time token learning model with worksheets to the students' competencies. This research is a quasi-experimental study (Quasi Experiment). The study population was firstrate Apikes Iris studentsÂ in general biology courses in the 2018/2019 school year. While the sample of this study was Apikes Iris level one local students A andÂ Local B as control class. The instruments used in the study were knowledge test questions, and attitude and skills observation sheets. Data analysis in this study used the t-test for knowledge competency and Mann Whitney U test, for attitude competency and skills. The results showed that the average value of learning competence of experimental class students was 80.03 better than control class students who were only 73.91. It can be concluded that the application of the learning model of the time token completed with student activity sheets has an effect on improving student learning outcomes.